Distribution of bone and muscle mass in water polo players - Iizuka, S.; Suguru, T.; Yukako, I. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
There are many previous studies demonstrating that different types of sports activity induce different distribution of bone and muscle in athletes. The knowledge about the composition of the elite athletes helps to build and maintain the body of young athletes. However, there is no report about the water polo players in Japan. In order to clarify the distribution on body composition of water polo players, we were compared with those in handball player and competitive swimmer. Methods: 20 male water polo players (WP: 19.7±1.3 years) and 29 male competitive swimmers (SW: 20.2±0.8 years) and male handball players (HB; 20.4±1.0 ) were recruited to this study, all of them were collegiate athletes. Body composition was assessed using dual X-ray absorptiometry (DXA). We compared their bone mineral content (BMC), bone mineral density (BMD) and lean mass (LM). Bone mineral mass and lean mass was adjusted by body height. Results: Bone mineral mass and density of the dominant arm of SM was significantly lower than those of WP and HD. However, those of the non-dominant were similar between three athlete groups. Thus, the side-to-side difference in arm BMC and BMD was lower in SM. For lean mass, there is no difference in each arm between the three athlete groups, and side-to-side difference in lean mass of the arm in WP was significantly larger than those of SW. On the other hand, BMC, BMD and LM of the leg of HD were significantly higher than those of SW and WP, and side-to-side difference in BMD of the leg was significantly larger in HD than those of WP. Discussion: It is considered that the higher BMC, BMD and lean mass in dominant arm of WP and HD were gained by their throwing motion. However, the higher lean mass in legs of HD seemed to be attained by weight bearing activity such as running and jumping, those not involved in activity of WP and SW. These results suggest that the mechanical stress imposed to specific body sites stimulate site-specific modeling and accumulation of bone and muscle.